Penerapan Strategi Index Card Match Untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa - Burhan, Ahmad (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2018)
The purpose of this study was to improve student learning activities and outcomes on Civics subjects by applying the Index Card Match strategy. The type of research used in this study is classroom action research. The procedure is carried out through two cycles, where each cycle consists of; (1) planning, (2) implementation (acting), (3) observation (observing), (4) reflection (reflecting). Collecting data in this study using student activity observation sheets, teacher performance observation sheets and test questions to measure student learning outcomes. The results of the study indicate that the application of the Index Card Match strategy can improve student learning activities and outcomes. This can be seen from the average activity of students in the first cycle (54.99%), in the second cycle (73.93%) there was an increase of (18.94%). The average student learning outcomes in the first cycle (61.78%), in the second cycle (67.5%) and an increase of 5.72%.